Undecyl 2,3-Dimethoxycinnamate from Daphne oleoides - Ullah, N. (Asian Journal of Chemistry, 2010)
Undecyl 2,3-dimethoxycinnamate, a new natural product, was isolated from the chloroform soluble fraction of the whole plant of Daphne oleoides. The structure of the new compound was established by modern spectroscopic methods.